Carbon Accounting for Enhanced Weathering - Amann, Thorben; Hartmann, Jens (Frontiers in Climate, 2022)
The inevitable deployment of negative emission technologies requires carbon accounting to incentivise the investment and to foster an active CO2 certificate trading schema. Enhanced Weathering as one of the negative emission technologies is being tested in the field now, but lacks a verifiable and cost-effective carbon accounting approach. Based on results from a lab scale column experiment and field observations, it is hypothesised that the observed stable positive correlation between total alkalinity and electrical conductivity may present a way to easily predict CO2 sequestration by chemical mineral weathering at low costs. Alkalinity is a measure to track weathering products. It is not difficult to measure, yet continuous sampling and analyses are expensive and time consuming. The observed strong correlation of alkalinity with electrical conductivity could be harnessed and enable a CO2 uptake monitoring by simple electrical conductivity measurements in soils or any point in the discharge system. For a successful implementation, databases need to be created, covering the most likely employment scenarios of soil, climate, rock product, application scenario and plant abundance.